Parental report of vaccine receipt in children with autism spectrum disorder: Do rates differ by pattern of ASD onset?. Issue 11 (8th March 2016) - Goin-Kochel, Robin P.; Mire, Sarah S.; Dempsey, Allison G.; Fein, Rachel H.; Guffey, Danielle; Minard, Charles G.; Cunningham, Rachel M.; Sahni, Leila C.; Boom, Julie A.
Highlights: Receipt of six childhood vaccines was compared across four patterns of autism onset. Vaccine receipt was equivalent between all autism-onset groups except for varicella. Those with delay-plus-regression onset had lower rates of varicella receipt. Mean rates of varicella receipt fell within the range of equivalence. Findings do not support a link between pattern of autism onset and vaccine receipt. Abstract: A contentious theory espoused by some parents is that regressive-onset of autism spectrum disorder (ASD) is triggered by vaccines. If this were true, then vaccine receipt should be higher in children with regressive-onset ASD compared with other patterns of onset. Parental report of rate of receipt for six vaccines (DPT/DTaP, HepB, Hib, polio, MMR, varicella) was examined in children with ASD ( N = 2755) who were categorized by pattern of ASD onset (early onset, plateau, delay-plus-regression, regression). All pairwise comparisons were significantly equivalent within a 10% margin for all vaccines except varicella, for which the delay-plus-regression group had lower rates of receipt (81%) than the early-onset (87%) and regression (87%) groups. Findings do not support a connection between regressive-onset ASD and vaccines in this cohort.